Main barriers and potential solutions in development of energy efficient buildings in warm climate of Iran - Hajigholami, Fereshteh (2017)
Iran is considered as one of the developing countries in the Middle East with high levels of energy consumption. Enhancing the energy efficiency of buildings can be regarded as a sustainable method of reducing the energy consumption and subsequently, the environmental impacts in Iran. Only a few buildings in Iran are constructed via using EE strategies, but they are built with less or unsuccessful operations and neglects in the implementation of EE technical solutions. The aim of this study is to identify the experiences of EEB in Iran especially in warm climate and identifying the barriers and drivers in the developing of EEBs in Iran. The study adopted a qualitative methodological approach and strategy in data collection and analysis. 8 EEBs and designs in Iran were selected as case studies. Qualitative method by using case study, observation, semi-structured interviews were used to interview architects of 8 EEBs and designs in Iran. Observations were conducted on these 8 case buildings for collecting evidences of neglect in their design, constructions and operation. semi-structured interviews were conducted among 16 architects to understand main barriers and drivers in the developing of EEB in Iran. Due to great diversity of barriers to finding and implementing solutions, it will be useful to group these barriers in some way which should not seen as rigid, but as a framework for identification and analysis. In gauging this understanding, a Trudgill (1990) framework for analysis consist of six major groups of barriers – agreement, knowledge, technological, economic, social and political was used. The study identified 63 barriers deterring the development and implementation of applying EE solutions in Iranian buildings and these were grouped into 8 categories: 1) Low energy prices in Iran, 2) Lack of interest by client for applying EE solutions in their building, 3) Applying EE solutions in building cost too much, 4) Lack of political will, legislation and enforcement, 5) Lack of technical understanding among project team members, 6) Lack of interest by project team members, 7) Lack of some of the EEB components on the Iran markets, and 8) Lack of leadership in EEB projects. For the solutions to overcome the obstacles 94 answers were suggested by 16 interviewees and these were grouped into 4 categories: 1) Action by government, 2) Action by education Sector, 3) Action by private sector, and 4) Action by Clients. The benefits of research is to identified the EEBs and their opportunities like economic benefits, environmental benefits, reduction in energy usage as well as one of the best strategic solutions for the decreased air pollution and global demand for energy etc. for the Iranian public and Iranian building industry players.